Geochronology and Depositional History of the Sandy Springs Aeolian Landscape in the Unglaciated Upper Ohio River Valley, United States - Purtill, Matthew P.; Kite, J. Steven; Forman, Steven L. (Frontiers in Earth Science, 2019)
The study of active and stabilized late Quaternary aeolian landforms provides important proxies for past climate events and environmental transitions. Despite an overall increase in the study of aeolian landforms in previously glaciated and coastal settings in eastern North America, the history of aeolian sedimentation in many unglaciated inland alluvial settings remain poorly understood. This study reports on the geochronology and depositional history of aeolian landforms and sediments in the unglaciated upper Ohio Valley at the Sandy Springs site. Aeolian landforms and sediments include complex, linear, barchan-like, and climbing dunes; an interdune sand sheet; and sandy loess that blankets high valley surfaces. At Sandy Springs, aeolian dune sands and sandy loess are restricted to intermediate (S2) and higher (S3) geomorphic surfaces. Eight optically stimulated luminescence age estimates constrain the initiation of aeolian processes on the S2 surface to sometime after 17 ka and episodic deposition on the S2 and S3 surfaces between 11 and 1.4 ka. The distribution of aeolian sediments at Sandy Springs is influenced by several past factors including local wind fetch potential, sediment availability, and underlying alluvial topography. Sediment availability is interpreted as the primary factor controlling aeolian processes and appear linked to several pan-regional paleoclimate events. Sandy loess deposition at ca. 8.2 ka on the S3 surface may reflect hydrologic variability and cooling, associated with the final pulse of meltwater into the North Atlantic from the Laurentide Ice Sheet. Dune reactivation and erosion at ca. 4.5 ka on the S2 surface indicate enhanced sediment availability possibly associated with drought conditions. These results illustrate that the deciphering the coupled fluvial-aeolian records in this catchment of the Ohio River provides new insight into the nature of changing surface processes against the backdrop of climate variability over the past ca. 20 ka.